2009
DOI: 10.1128/iai.00802-08
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor 3 Deficiency Influences Lesion Progression duringLeishmania majorInfection in BALB/c Mice

Abstract: Leishmania major is an obligately intracellular protozoan parasite that causes cutaneous leishmaniasis. Like numerous intracellular pathogens, Leishmania exploits cell surface receptors as a means of entry into host cells. Complement receptor 3 (CR3; also called CD11b/CD18), a ␤ 2 integrin on phagocytic cells, is one such receptor. Ligation of CR3 has been shown to inhibit the production of interleukin-12, the cytokine that is pivotal in establishing the cell-mediated response necessary to combat intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 62 publications
(49 reference statements)
1
21
1
Order By: Relevance
“…Interestingly, the interaction of Leishmania to Mac-1 results in silent entry of the parasite into the phagocytes, thereby avoiding the activation and release of reactive oxygen intermediates and subsequent lysis of the parasites (43,44). Also, a report showed that Mac-1-deficient C57BL/6 mice display similar lesions and parasite burden as WT mice postinfection with L. major (45). Although this observation is inconsistent with our findings, it is conceivable that Mac-1 is a functionally redundant pathway that becomes important only in the absence of CD40-CD40L interaction.…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, the interaction of Leishmania to Mac-1 results in silent entry of the parasite into the phagocytes, thereby avoiding the activation and release of reactive oxygen intermediates and subsequent lysis of the parasites (43,44). Also, a report showed that Mac-1-deficient C57BL/6 mice display similar lesions and parasite burden as WT mice postinfection with L. major (45). Although this observation is inconsistent with our findings, it is conceivable that Mac-1 is a functionally redundant pathway that becomes important only in the absence of CD40-CD40L interaction.…”
Section: Discussioncontrasting
confidence: 57%
“…We and others have demonstrated that IgG-opsonized amastigote uptake occurs primarily through an FcRγ-mediated process, whereas C3bi-opsonized promastigote uptake occurs primarily through a CR3-mediated process (Carter et al, 2009;Kima et al, 2000;Mosser and Edelson, 1985;Russell and Wright, 1988;Ueno and Wilson, 2012). SFKs are known to facilitate immunoglobulinmediated phagocytosis.…”
Section: Sfks Are Required For Efficient Amastigote But Not Promastigmentioning
confidence: 99%
“…Functionally, the C11b hi subset of dDCs could potentially be involved in susceptibility, as mice lacking CD11b (complement receptor 3) fared marginally better than their wild type BALB/c counterparts. This is likely due to the fact that in the CD11b knock-out mice, the CD11b hi subset of cells are still present but do not express the integrin [54]. However, this study focused on CD11b expression on macrophages and neutrophils, while CD11b expression on the Langerin À subset of dDCs could also contribute to this effect.…”
Section: Reviewmentioning
confidence: 56%